A review of approaches for dental practice teams for promoting oral health. Issue 4 (19th February 2016) - Kay, Elizabeth; Vascott, Donna; Hocking, Allice; Nield, Helen; Dorr, Charles; Barrett, Helen
Abstract: To determine the circumstances in which oral health promotion (OHP) in General Dental Practice is at its most effective, a systematic review was conducted to identify, critically appraise and synthesize the available evidence. The research question was: Is oral health promotion within dental practice effective and how can its effects be optimized? Systematic searches of 20 online resources (including Ovid Medline and Embase) were conducted. A call for evidence was also issued, and citation lists of other relevant systematic reviews were included. All studies published since 1994 which were set in the context of general dental practice and investigated promoting good oral health in adult or child patients were considered. 44 studies reported in 52 papers were included in the review. The evidence was heterogeneous and the quality of reporting was variable. Results showed that oral health promotion based on behavioural and psychological models was effective for improving oral health. Verbal advice affected knowledge and reported behaviour, written advice promoted oral health knowledge. There was moderate evidence that the attributes of the 'sender' of an oral health promotion message influenced its effectiveness. Many barriers and facilitators were shown to influence the effectiveness of OHP in dental practice. The results of this review suggest that the psychology of behaviour change is the key to oral health promotion and greater emphasis on teaching oral health professionals about health psychology would make oral health promotion in the dental surgery more effective.